Mittag-Leffler Operator Connected with Certain Subclasses of Bazilevic̆ Functions - Om Ahuja; Asena Çetinkaya; Naveen Kumar Jain (Journal of Mathematics)
In this paper, we introduce a new generalized class of analytic functions involving the Mittag-Leffler operator and Bazilevic̆ functions. We examine inclusion properties, radius problems, and an application of the generalized Bernardi–Libera–Livingston integral operator for this function class.